A mathematical modeling of the impact of proliferation of arms and weapons on Nigeria and control - Kambai*, S.A.; Durojaye†‡, M.O.; Abah*, R.T. (International Journal of Mathematical Analysis and Modelling, 2023)
The proliferation of arms and weapons is a kind of terrorism against humanity that has claimed the lives of many Nigerians, rendered many homeless, made widows and widowers, and forced the closure of companies as a result of ransom demanded for hostages by kidnappers. As a result, a detailed investigation into the cause of the growth of light weapons utilized and how it assists kidnapping activities is in great demand. In this paper, we utilize a compartmental deterministic model to investigate the dynamics of small and light weapon proliferation and kidnapping in Nigeria. A mathematical model was developed on the impact of the proliferation of arms and weapons used in kidnapping activities, as a system of nonlinear differential equations. We established the existence of solution and equilibrium state for the model and discussed its global stability. The model was analyzed numerically using the fourth-order Runge-Kutta method. Graphical results showing the effects of detention, imprisonment, and rehabilitation on kidnapping activities are given. The results show that kidnapping activities can be reduced through the control of the importation of small arms and light weapons.